A novel Mosquitoes Repellent Soap based on Azadirachta Indica and Eucalyptus Citriodora oil - Khairul Farihan, Kasim; Harbant, Singh; Mohamed Murray Hunter; Mohd Noor, Ahmad (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my